2011
DOI: 10.1111/j.1365-2206.2010.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Homeless young people, families and change: family support as a facilitator to exiting homelessness

Abstract: A B S T R AC TThe families of homeless young people are most often portrayed as a precipitating factor in their homelessness. However, recent studies, particularly those taking a longitudinal approach, have drawn attention to the enabling role of family members and their positive influence on the housing trajectories of homeless youth. Drawing on selected findings from an ongoing longitudinal qualitative study of homeless young people in Dublin, Ireland, this paper aims to build on this relatively fertile area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 35 publications
1
55
0
4
Order By: Relevance
“…51Á53). Indeed, the overriding theme of difficult family relationships and home lives Á punctuated by personal issues of substance misuse and mental illness, and/or experiences of abuse and trauma Á is widely recognised in the literature as one important aspect of the 'story' of youth homelessness (see, e.g., Mallett et al 2009, Milburn et al 2009, Mayock et al 2011, Barker 2012. At the same time, it is important not to over-simplify home leaving as an explicit 'choice' or indicator of agency amongst this group of young people (Jones 1995, pp.…”
Section: Interrupted Lives: Journey(s) Towards Couch Surfingmentioning
confidence: 99%
“…51Á53). Indeed, the overriding theme of difficult family relationships and home lives Á punctuated by personal issues of substance misuse and mental illness, and/or experiences of abuse and trauma Á is widely recognised in the literature as one important aspect of the 'story' of youth homelessness (see, e.g., Mallett et al 2009, Milburn et al 2009, Mayock et al 2011, Barker 2012. At the same time, it is important not to over-simplify home leaving as an explicit 'choice' or indicator of agency amongst this group of young people (Jones 1995, pp.…”
Section: Interrupted Lives: Journey(s) Towards Couch Surfingmentioning
confidence: 99%
“…It is well documented that those who receive financial and emotional support are more able to make the transition from homelessness to domicile. 6,[22][23][24][25] Furthermore, evidence suggests that the more social supports a person has, the fewer episodes of homelessness they experience. 26 This finding underscores the importance of family and friends in determining health and length of homelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Many have experienced family conflicts and are without strong family support. The few studies of their pathways out of homelessness have found that positive outcomes are associated with returning to the family home, engagement in education, training and employment and help from family and professionals (Kurtz et al, 2000;Milburn et al, 2007Milburn et al, , 2009Nebbitt et al, 2007;Mallett et al, 2010;Mayock et al, 2011;Tevendale et al, 2011). The few studies of their pathways out of homelessness have found that positive outcomes are associated with returning to the family home, engagement in education, training and employment and help from family and professionals (Kurtz et al, 2000;Milburn et al, 2007Milburn et al, , 2009Nebbitt et al, 2007;Mallett et al, 2010;Mayock et al, 2011;Tevendale et al, 2011).…”
Section: Resettlement For Homeless Young Peoplementioning
confidence: 99%